2010
DOI: 10.1088/0004-637x/718/1/199
|View full text |Cite
|
Sign up to set email alerts
|

A MEASUREMENT OF SMALL-SCALE STRUCTURE IN THE 2.2 ⩽z⩽ 4.2 Lyα FOREST

Abstract: The amplitude of fluctuations in the Lyα forest on small spatial scales is sensitive to the temperature of the intergalactic medium (IGM) and its spatial fluctuations. The temperature of the IGM and its spatial variations contain important information about hydrogen and helium reionization. We present a new measurement of the small-scale structure in the Lyα forest from 40 high resolution, high signal-to-noise ratio, VLT spectra for absorbing gas at redshifts between 2.2 z 4.2. We convolve each Lyα forest spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
286
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(322 citation statements)
references
References 77 publications
(240 reference statements)
33
286
3
Order By: Relevance
“…This provides constraints on the integral optical depth to the CMB last scattering surface, indicating that reionization must have been under way by z ∼ 11 (Planck Collaboration 2013; Bennett et al 2013); this assumes instantaneous reionization, which is unlikely to be a realistic scenario. Measurements from the thermal history of the IGM are consistent with this figure (Theuns et al 2002;Bolton et al 2010;Lidz et al 2010). …”
Section: Introductionsupporting
confidence: 79%
“…This provides constraints on the integral optical depth to the CMB last scattering surface, indicating that reionization must have been under way by z ∼ 11 (Planck Collaboration 2013; Bennett et al 2013); this assumes instantaneous reionization, which is unlikely to be a realistic scenario. Measurements from the thermal history of the IGM are consistent with this figure (Theuns et al 2002;Bolton et al 2010;Lidz et al 2010). …”
Section: Introductionsupporting
confidence: 79%
“…However, there is generally a lack of consistency between these measurements and those from other studies (Ricotti et al 2000;McDonald et al 2001;Zaldarriaga et al 2001;Lidz et al 2010). In particular Lidz et al (2010) found evidence for a much hotter IGM at z 3.5 than expected from current models (Puchwein et al 2015;Upton Sanderbeck et al 2016;Oñorbe et al 2016), in disagreement with Becker et al (2011).…”
mentioning
confidence: 68%
“…Irrespective of the nature of these sources, if they reionized intergalactic helium at z 4, these sources also likely contributed substantially to H I reionization (Madau & Haardt 2015). Unfortunately, it is not currently possible to probe the ionization state of He II via far-UV He II Lyα absorption at z 4, and constraints on He II reionization from the thermal state of the IGM do not all agree (Lidz et al 2010;Becker et al 2011;Upton Sanderbeck et al 2016). This paper introduces a new method to constrain the timing of He II reionization.…”
mentioning
confidence: 99%
“…This relation is established ∆z ∼ 1 − 2 after the end of cosmological reionization processes (Hui & Gnedin 1997;Trac et al 2008;Furlanetto & Oh 2009;McQuinn et al 2009). Motivated by this limiting behavior, a power-law parameterization for the thermal state is adopted in almost all analyses of the Lyα forest (e.g., McDonald et al 2005;Viel et al 2006;Lidz et al 2010). 1 Here we provide a simple explanation for the physics that sets the asymptotic relation as well as an understanding for how quickly this asymptote is reached.…”
Section: Introductionmentioning
confidence: 99%